Run Silent, Run Cheap: Deciding on the Oberon-class Submarines, 1960–68 - Adomeit, Ambjörn L. (The Northern Mariner / Le marin du nord, 2025)
During the looming crisis of the early Cold War, the Supreme Allied Commander Atlantic of the North Atlantic Treaty Organization wanted Canada to procure a subsurface capability of equal quality, if not quantity, to that of other Allied nations. Even though Canada played with acquiring nuclear submarine technologies and several new conventionally powered hunter-killer submarines, politicians were more interested in cutting costs and using as few funds as possible to cover as many roles as possible. Canada opted to purchase three operational submarines to help fill anti-submarine warfare roles, but the Oberon-class boats that were ultimately chosen by the end of the 1960s were entirely obsolete and were by that time the only choice available to Canada’s politicians: Canada’s dithering had cost its navy its best options for subsurface capabilities. This paper recounts in detail the depths to which federal dithering on the submarine issue of the 1960s sank, a process that in turn nearly scuttled Canada’s submarine program.